Long term : essays on queer commitment - Herring, Scott, 1976-; Wallace, Lee, 1962-; Johnson, E. Patrick, 1967- (Duke University Press, 2021)
"The contributors to Long Term use the tension between the popular embrace and legalization of same-sex marriage and the queer critique of homonormativity as an opportunity to examine the myriad forms of queer commitments and their durational aspect."--